(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research explores how speech acts function within the scope of intercultural communication, with a particular emphasis on the linguistic and cultural interactions between Uzbekistan and English-speaking environments. It highlights the differences in communication styles, especially in the context of resolving conflicts. The findings reveal that Uzbek speakers typically employ indirect and polite forms of expression, influenced by collectivist values and a respect for social hierarchy. In contrast, English speakers often use more direct and explicit communication, reflecting the norms of low-context cultures. Gaining insight into these contrasts is crucial for enhancing cross-cultural communication and promoting respectful and effective exchanges across languages.